Potassium Permanganate–Oxidized Nanocellulose: Structural Features and Rheological Performance for Advanced Applications - Kuzieva, M.M.; Urishova, F.M.; Atakhanov, A.A.; Ashurov, N.Sh.; Rashidova, S.Sh.; Shiman, D.I.; Kostjuk, S.V.; Kang, S. (Eurasian Journal of Chemistry, 2025)
The development of environmentally friendly strategies for nanocellulose modification is crucial for advancing biomedical materials. Traditional oxidation methods often involve costly or toxic reagents, limiting largescale use. This study addresses this by preparing oxidized nanocellulose (ONC) from microcrystalline cellulose using an eco-friendly acidic potassium permanganate (KMnO4) oxidation method to introduce surface carboxyl groups. Structural and morphological changes were characterized through FTIR, XRD, SEM, and DLS analyses, which confirmed successful oxidation, retained fibrillar morphology, and altered crystallinity and surface charge. Hydrogel formulations were developed from ONC suspensions, and their rheological properties were assessed through frequency and amplitude sweeps. FTIR spectra confirmed the introduction of carboxyl groups, while XRD revealed reduced crystallinity and lattice expansion with oxidation. DLS demonstrated narrower size distributions at intermediate oxidation times, indicating improved dispersion stability. SEM images confirmed retention of fibrous morphology with reduced fibril widths. Rheological tests showed that ONC hydrogels exhibited shear-thinning and gel-like behavior (G′ > G″), displaying the highest storage modulus and broadest linear viscoelastic region, consistent with a strong and stable gel network. ONC-based hydrogels show significant promise for biomedical applications, including mucoadhesive drug delivery, wound healing, and tissue engineering.
Keywords: oxidized nanocellulose; microcrystalline cellulose; permanganate oxidation; carboxyl functionalization; structural characterization; hydrogel; rheological properties; drug delivery systems